The Role of Saudi Universities in Society Awareness-Raising of Harmful Effects of Narcotics and Preventive Methods (A Field Study) - Saud Eid Alanazi (University of Science and Technology, Yemen, 2016)
Abstract: The study aimed to identify the role of Saudi universities to raise the society's awareness of harmful effects of narcotics and how to prevent such effects. The study population consisted of all teaching staff members of Saudi Universities, from science and humanities  during the academic year 2012-2013. The sample was randomly selected from these universities: King Faisal, Northern Border, Jizan and Tabuk), consisting  of (150) faculty members from each university. For that purpose a questionnaire of 25 items was developed, and  appropriate statistical methods were used to analyze the data. The study revealed that the role of Saudi universities in facing the problem of narcotics was (moderate) from the faculty members' perspectives; the roles of combating narcotics where in the following order:   - Awareness-raising role came in the first rank: the university role was high.  - Protective came in the second rank: the university role was moderate. - Educational came in the second rank: the university role was moderate.  In addition to such roles, there were ostensible statistical differences between the means and standard deviations in the role of Saudi universities in combating narcotics due to the different levels among the study variables (university, specialization, gender).